Need and access to assistive technology in Italy: results from the rATA survey. - Desideri, Lorenzo; Magni, Riccardo; Guerreschi, Massimo; Bitelli, Claudio; Hoogerwerf, Evert-Jan; Vaccaro, Concetta; Taruscio, Domenica; De Santis, Marta; Romeo, Rosa Immacolata; Capuano, Elena Ilaria; D'Avenio, Giuseppe; Morelli, Sandra; et al. (Disability & Rehabilitation: Assistive Technology, 2025)
Purpose: This study assessed the prevalence of assistive products need, use, and access in Italy using the rapid Assistive Technology Assessment (rATA) tool. Materials and Methods: Conducted from June to September 2021, the survey involved a random sample of 10167 Italian citizens. Stratified sampling was used to ensure that the sample involved was representative of the Italian population. A combination of Computer Assisted Telephone Interviewing (CATI) and Computer Assisted Web Interviewing (CAWI) was used. Results: The estimated prevalence of need in the population resulted of 52,6% with 45,8% reporting their needs as met and 6,7% experiencing unmet needs. Use and need were higher among older adults (60+ years). Logistic regression indicated that respondents aged 60+ (OR: 3,3; 95% CI: 2,8-3,8) and respondents reporting more severe functional difficulties (OR: 23,9; 95% CI: 19,4-29,6) are more likely to be users of assistive products. Younger respondents (0-17 years old) reported using on average more assistive products (M = 2,7; SD = 2,9) than adults (M = 1,6; SD = 1,7) and older users (M = 1,6; SD = 1,5) (all ps <.001). Notably, mobile digital devices (smartphones/tablets) are the second most used assistive products, preceded by spectacles and followed by pill organizers. Conclusions: This study provides essential baseline data to inform policies and improve AT access nationwide. The results highlight the importance of recognizing mainstream digital devices, such as commercially available smartphones, as legitimate assistive products. Secondary analyses will contribute to strengthen the understanding of factors associated to successful AT provision. IMPLICATIONS FOR REHABILITATION: AT needs in Italy are highest among older adults, especially for functional limitations related to aging. Children and adolescents use more AT products than other groups. Mainstream devices like smartphones are frequently used as AT solutions.